2016
DOI: 10.1111/jce.13114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ventricular Arrhythmia Ablation in Patients With Heart Mate II Left Ventricular Assist Devices: An Evaluation of Ablation Therapy

Abstract: In patients with progressive HF and LVAD implantation, ablation is associated with reduced VA rates. In LVAD patients, most VAs arise from substrate unrelated to the inflow cannula site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Indeed, multiple studies reported that the majority of ventricular arrhythmias ablated in the LVAD population are related to scar remote form the LVAD canula. (10)(11)(12)(13). While pre-LVAD was an independent predictor of late post LVAD VA, early post LVAD VA was not after adjusting for pre-LVAD VA.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, multiple studies reported that the majority of ventricular arrhythmias ablated in the LVAD population are related to scar remote form the LVAD canula. (10)(11)(12)(13). While pre-LVAD was an independent predictor of late post LVAD VA, early post LVAD VA was not after adjusting for pre-LVAD VA.…”
Section: Discussionmentioning
confidence: 82%
“…Elsewhere, while LVAD therapy has emerged as a promising option to improve survival in patients with endstage heart failure, it has been repeatedly reported that LVADs may actually increase the VA burden. 4 In a single-center retrospective analysis of 43 patients who underwent implantation of a HeartMate™ II LVAD (Abbott Laboratories, Chicago, IL, USA), 27.9% experienced early electrical storm, defined as three or more ICD therapy applications in 24 hours, with a median time from LVAD implant of 9.1 days ± 7.8 days. Those who had early VT also had a significantly higher all-cause mortality rate at 30 days (33.3% versus 6.5%).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well-recognized that ventricular arrhythmia (VA) burden may actually rise following the implantation of an LVAD, 2 which is associated with a decrease in patient survival. 3 Catheter ablation for recurrent, drug-refractory ventricular tachycardia (VT) in patients with structural heart disease is well-established, [4][5][6] resulting in fewer appropriate implantable cardioverter-defibrillator (ICD) shocks and repeat hospitalizations. In this report, we discuss the case of a patient with drug-refractory VA following LVAD placement that was successfully mapped and terminated with catheter ablation.…”
Section: Introductionmentioning
confidence: 99%
“…With the older generation HeartMate LVAD, VA after LVAD placement was thought to involve substrate around the apical inflow cannula in many cases, but analysis was largely based on 12 lead EKG localization . Small, early series of endocardial VT ablation after LVAD placement suggested that VT is not associated with the apical inflow cannula in a majority of cases . More recent, larger series including continuous flow LVAD models have confirmed that late VT is often associated with pre‐existing intrinsic scar remote from the inflow cannula, and catheter ablation in these areas terminates over half of induced VT, whereas cannula‐associated arrhythmia accounted for only 9% to 24% of cases …”
Section: Discussionmentioning
confidence: 99%
“…Postimplant VA has been associated with right HF and increased mortality, and they are more prevalent in patients with older age, nonischemic cardiomyopathy (NICM), preoperative VA, and atrial fibrillation (AF) . Several studies have demonstrated the feasibility of endocardial mapping and ablation after LVAD placement . However, ventricular tachycardia (VT) ablation post‐LVAD can be limited by the inability to safely obtain percutaneous epicardial access, and VT recurrence rates after endocardial ablation are between 24% and 38%.…”
Section: Introductionmentioning
confidence: 99%